Sowing for food security: A case study of smallholder farmers in Bolivia. (December 2016) - Salazar, Lina; Aramburu, Julián; González-Flores, Mario; Winters, Paul
Highlights: This paper presents the link between agricultural interventions and food security. The analysis assesses the impact of a technology adoption program in Bolivia. Participation improved productivity, agricultural sales and household income. Food security improved through higher food access and availability. Abstract: This paper explores the role that agriculture can play in the food security agenda. To meet this objective, this study measures the impact of the "Programa de Apoyos Directos para la Creación de Iniciativas Agroalimentarias Rurales" (CRIAR), an agricultural technology adoption program implemented in highly food insecure areas of rural Bolivia. The paper analyzes whether changes in food security are due to improved food availability (production and local sales) and/or greater food access (income and production used for home consumption). To this end, data from a sample of 1287 households-817 beneficiaries and 470 controls – interviewed specifically for this purpose are used. To address self-selection issues, the program's impact is estimated using an instrumental variable model. The results present evidence that program participation improved food security. Specifically, positive impacts on agricultural productivity, agricultural sales and household income are found. These findings confirm the importance of considering agricultural programs as policy tools to address food insecurity.